G. Howard Ferguson : Ontario tory - Oliver, Peter, 1939- (Ontario historical studies series., 1977)
Peter Oliver's study of Ferguson's life and times provides both a revealing picture of a political professional of driving ambition and rare talent and a commentary on a largely rural society dealing with the challengers of industrialization and urbanization.